Formation of Films of Alloys of Cr–Ni, Cr–Ni–Si and Fe–Ni Systems by Sublimation and Evaporation Methods for Electronic Products - V. A. Zelenin; E. O. Narushko; A. D. Gladinov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
The processes of formation of films of alloys of the Cr–Ni, Cr–Ni–Si and Fe–Ni systems with a stab le elemental composition by evaporation methods are considered. It is shown that due to the large difference in the melting temperatures of Ni and Cr, nichrome films are obtained by sublimation. The design of the evaporator is proposed, which makes it possible to stabilize the composition of the films. Calculations of azeotropic compositions of alloys of the Cr–Ni–Si system have been carried out. The position of the isobars of the total pressure of iron and nickel on the state diagram was determined during evaporation in vacuum. The azeotropic composition of the alloy of the Fe–Ni system was calculated and experimentally verified.